Life-Threatening Rupture of a False Aneurysm after Femoral Arterial Catheterization: Unexpected Delay after a Common Procedure - Julie Renner; Pierre Pasquier; Elisabeth Falzone; Faye Rozwadowski; Stéphane Mérat (Case Reports in Vascular Medicine)
We report the case of a 79-year-old patient who presented with a femoral iatrogenic pseudoaneurysm of delayed and unusual onset with immediately life-threatening massive bleeding. Ultrasound is the method of choice for the diagnosis of pseudo aneurysm. If there is not spontaneous closure, ultrasound-guided compression repair, minimally invasive percutaneous treatments, and surgical repair are the three therapeutic options.